ANALISIS PENGHEMATAN NILAI WAKTU TEMPUH DAN BIAYA OPERASIONAL KENDARAAN PADA RENCANA PEMBANGUNAN JALAN KRUENG MEUSAGOP-TEUPIN MANE - Afrizal Afrizal; Sofyan M Saleh; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Growth and development of the city or region has implications for the increasing needs of the population. With the increase of population requirement, it will also increase the demand of travel in the form of increased movement activity of people and goods in a region or city, where the activity of this movement absolutely requires adequate transportation facilities and infrastructure both in quality and quantity. This study aims to determine the amount of time cost savings and operational costs of vehicles on alternative roads Krueng Meusagop-Teupin Mane. The data obtained in the form of primary data and secondary data. Primary data are traffic volume and speed data. While secondary data in the form of image data planning, location map, and cost budget plan data. Based on the result of the research, it is found that the operational cost savings of vehicle (BOK) if traffic flow passes Jalan Krueng Meusagop - Teupin Mane Rp 458 / vehicle for passenger car, Rp 1.723 / vehicle for bus and Rp 1.416 / vehicle for truck with BKBOK obtained in the 25th year is Rp. 1,009,412,291,578. while the savings of travel time value obtained if the traffic flow passes through Jalan Krueng Meusagop - Teupin Mane is Rp 21,877 / vehicle for passenger car, Rp 193.229 / vehicle for bus and Rp 24,048 / vehicle for truck with the value of time obtained in year the 25th of Rp. 993.214.592.528.Therefore, the construction of Krueng Meusagop - Teupin Mane Road is very feasible to be built for the achievement of regional development from isolation and also become an alternative way of society from the central region of Aceh if the road in Bireuen City will be congestion.